The Legal Legislation and the Law Enforcement Technique in the Conditions of Development of Information Systems - AVDEEV, Vadim Avdeevich; AVDEEVA, Olga Anatolievna; KULESHOV, Yury Ivanovich; BYKOV, Anton Vitalyevich; KISELEV, Evgeny Aleksandrovich; AKSENOV, Alexey Nikolaevich (Journal of Advanced Research in Law and Economics; Vol 10 No 1 (2019): JARLE Volume X Issue 1(39) Spring 2019DO - 10.14505//jarle.v10.1(39).05, 2019)
In modern conditions, one of the topical issues is the improvement of methods and means of legal technique. The development of lawmaking activities naturally led to the emergence of new tools and techniques of legal technology. The significance of the problem of improving the legal technique lies in the development of legal norms and the preparation of legal documents that must comply with the current rules and methods of filing legal materials. Techniques of legal technology imply the formulation of regulatory prescriptions taking into account the terminological unity of legal concepts. Means of formulating the norms of legal acts are the use of legal structures, legal definitions, notes, references, legal symbols and etc. The use of techniques and methods of systematization of regulatory legal acts (accounting, consolidation, incorporation, codification) is updated. The mastery of legal technique is evidence of the high general and legal culture of legislators, their professionalism and competence. It allows you to create effective regulatory legal acts.